The Effectiveness of Reality Group Counseling (WDEP) in Reducing Truancy Behavior among Students of MA Tunas Pertiwi Cirebon - Faqihudin Faqihudin (Asesment : Journal Of Counseling Guidance, 2026)
Background: Truancy is a global educational concern; in Indonesia, it is associated with poor academic performance and dropout. MA Tunas Pertiwi, a pesantren-based boarding school in Ciwaringin, Cirebon, showed high truancy rates despite its religious environment, with no dedicated BK teacher and no prior counseling intervention.Objective: This study aims to determine the effectiveness of WDEP Reality Group Counseling in reducing truancy among Class XI students at MA Tunas Pertiwi and assess the significance of behavioral change.Method: A quantitative pre-experimental one-group pretest-posttest design was employed. Seven male Class XI students were selected via purposive sampling. The WDEP intervention comprised 7 sessions (November–December 2023). Data were collected using a validated 32-item questionnaire (Cronbach’s Alpha = 0.704) and analyzed with paired-samples t-test (SPSS 27.0).Findings and Implications: Results showed t = 10.842 (t-table = 1.895), p = 0.000 (p < 0.05). Mean pretest score was 96.0 (SD = 4.55; very high–high) and declined to 81.7 (SD = 7.95; high) post-intervention—a reduction of 14.3 points (14.9%), confirming intervention effectiveness. Students also demonstrated improved personal responsibility and truancy awareness.Conclusion: WDEP Reality Group Counseling effectively reduces truancy at MA Tunas Pertiwi. Schools without BK teachers should adopt this structured approach. Future research using larger samples and controlled designs is encouraged to strengthen generalizability.